PESANTREN DAN PENDIDIKAN KARAKTER DI PONDOK PESANTREN KHALAF - Amirudin, Ja'far; Suhartini, Andewi; Basri, Hasan; Rohimah, Elis (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2025)
This research aims to explain the meaning and labeling of khalaf or modern in Islamic boarding schools and how to build character or character building in modern Islamic boarding schools. This research uses the library research method using article study materials through journals, theses, theses and books. Character education is the cultivation of habits that are carried out in a continuous, measurable and directed manner to form a good, honest, strong and independent personality. In some advanced and modern Islamic boarding schools (in which there is formal education, even up to universities) they usually apply high discipline and there are also those who apply semi-military discipline. In the development of Islamic boarding schools and character education in modern Islamic boarding schools, it has become a trend in itself, especially in terms of learning, which generally uses modern technology with a curriculum that combines the Islamic boarding school curriculum with the curriculum in formal and even international schools. In terms of language, modern Islamic boarding schools generally use Arabic and English. From the results of the author's literacy study, it can be concluded that character education at the Khalaf Islamic boarding school in each institution has the following characteristics: instilling high discipline, familiarization with foreign languages, students increasing their extracurricular activities, learning using modern technology, expensive entrance fees and tuition fees, high standards for graduates. talent, orientation is more towards utilizing the competencies of students and generally the management of the Khalaf Islamic boarding school is well structured